O Programa Territórios da Cidadania e o desenvolvimento rural sustentável - Brito, Ana Vládia da Costa (2012)
Given the spread of the term sustainable rural development, the territorial approach has become an alternative to transform the normative ideal contained in the idea of developing something operating through public policies, such as the Citizenship Territories Program (CTP). This program originated in 2008 with the objective to promote and accelerate the elimination of poverty and social inequalities in rural areas. Since then it has implemented in all Brazil, with ministries, federal and state agencies, government representatives, municipal and civil society, series of actions in 120 territories. This research proposes to identify the importance of the CTP to sustainable rural development in the state of Ceara. The study area encompasses the six Territories of Citizenship of the State of Ceara. The analysis of levels of sustainability of the Territories of Citizenship occurred through aggregate indices for each dimension of sustainable development. Initially it was constructed a matrix of indicators with information regarding the 100 municipalities included in the Territories of Citizenship in the state of Ceara. Therefore, they were selected indicators of sustainability with a greater connection with the actions proposed by PTC. In total it selected 35 (thirty five) indicators derived from secondary data provided by the Brazilian Institute of Geography and Statistics (IBGE), the Institute of Economic Research and Strategy of Ceara (IPECE), the Department of the Unified Health (DATASUS) and National Institute for Educational Studies and Research AnísioTeixeira (INEP). Data regarding the number of shares and amount invested in each territory from Ceara were obtained from the Program Execution Reports. The survey results show that the CTP during the study period, contributing to sustainable rural development. However, no proven direct relationship between the amounts invested by the program and feedback on those aspects that should be affected by such investments. The social dimension, which received the largest amount of investment, has not undergone significant changes in their levels of development and there are even reverse if the territories of Cariri, Sertoes of Caninde and Valleys Curu and Aracatiaçu. It was also an unequal distribution of shares and investment between the dimensions analyzed, verifying the need for better targeting of program resources in relation to the dimensions of sustainability.